2014
DOI: 10.14814/phy2.12023
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nicotinic exposure produces a depressed hypoxic ventilatory response and subsequent death in postnatal rats

Abstract: In this study, we asked whether a “full term” prenatal nicotinic exposure (fPNE, 6 mg·kg−1·day−1 nicotinic delivery) over the full gestation, compared to a traditional PNE (tPNE) over the last two‐thirds of the gestation, caused a higher mortality following a remarkable depressed hypoxic ventilatory response (dHVR) independent of brain and pulmonary edema and change in serum corticosterone. P12‐14 pups pretreated with tPNE, fPNE or their vehicle (tCtrl and fCtrl) were exposed to 5% O2 for up to 60 min followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 64 publications
(93 reference statements)
5
16
0
Order By: Relevance
“…, 2000; Hafstrom et al , 2002). We previously showed that PNE significantly prolonged the apneic response and augmented pulmonary C-neural response to right atrial injection of capsaicin, proving the PNE-induced PCF plasticity (Zhuang J, 2014). Because PCF activation depresses hypoxic and hypercapnic ventilation that could be responsible for respiratory failure (see discussion in ref.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…, 2000; Hafstrom et al , 2002). We previously showed that PNE significantly prolonged the apneic response and augmented pulmonary C-neural response to right atrial injection of capsaicin, proving the PNE-induced PCF plasticity (Zhuang J, 2014). Because PCF activation depresses hypoxic and hypercapnic ventilation that could be responsible for respiratory failure (see discussion in ref.…”
Section: Discussionmentioning
confidence: 86%
“…Our recent studies have shown that PNE sensitizes PCFs and prolongs the apneic response to right atrial bolus injection of capsaicin (Zhuang J, 2014). However, the mechanisms underlying this PNE modulation is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations